Probiotic (Enterococcus faecium) induced responses of the hepatic proteome improves metabolic efficiency of broiler chickens (Gallus gallus). (December 2016) - Zheng, Aijuan; Luo, Jianjie; Meng, Kun; Li, Jianke; Bryden, Wayne; Chang, Wenhuan; Zhang, Shu; Wang, L.; Liu, Guohua; Yao, Bin
Abstract Background The liver plays important roles in nutrient metabolism, detoxification and immunity.Enterococcus faecium (E. faecium ) is a probiotic that has been shown to have positive effects on broiler production. However, its molecular effects on liver metabolism have not been characterized. This study aims to further identify the biological roles ofE. faecium by characterizing the hepatic proteomic changes of broilers (Gallus gallus ) fedE. faecium using two-dimensional fluorescence difference gel electrophoresis (2-D DIGE) and mass spectrometry (MS). Results Thirty-three proteins (50 protein spots) involved in nutrient metabolism, immunity and the antioxidant system were shown to be differentially expressed in the liver of broilers fedE. faecium than from birds not fed the probiotic. The biological processes of sulphur amino acids, vitamin and cellular hormone metabolism, sulphur compound biosynthesis and protein tetramerization were enhanced in the liver of broilers fedE. faecium . However, proteins involved in calcium ion flux, cell redox homeostasis and platelet activation related to hepatic immune responses were down-regulated in broilers fedE. faecium . These results indicate that the supplementation of poultry feed withE. faecium may alter the partitioning of nutrients and promote optimal nutrient utilization. Conclusions This study assists in unraveling the molecular effects of the dietary probiotic, E. faecium, in the liver of broiler chickens. It shows that the probiotic improves the metabolism of nutrients and decreases inflammatory responses. Our findings extend previous knowledge of the mechanism of dietary probiotic action and provide new findings for research and future probiotic development.